PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. PEGADAIAN (PERSERO) CABANG SELONG - Saputra, Didin Hadi (Jurnal Magister Manajemen, 2015)
The Services at the pawning house of PT. Pegadaian ( Ltd ) of Selong Branch Office are mostly pawning service. Pawning service is one of the main services provided by PT. Pegadaian (Ltd) of Selong Branch Office. This study aims at observing five variables to identify customers’ satisfaction. Those five variables are reliability (X1), responsiveness (X2), assurance (X3), emphaty (X4), and tangibles (X5). This is an associative study using quetionnaires for data collection. Data is then analyzed the multiple linear regression analysis. The study reveals that the variables of reliability (X1), responsiveness (X2), assurance (X3), emphaty (X4), and tangibles (X5) both simultaneously and separately have a significant and positive effect towards customers’ satisfaction. This, the hypothesis of the study is accepted. Accordingly, PT. Pegadaian (Ltd) of Selong Branch Office is to maintain the implementation of the five variables. Also, it is also suggested that PT. Pegadaian (Ltd) of Selong Branch Office improve the tangible facilities such as suggestion box, AC, trash cans, and the space layout. Keywords : services, customer’ satisfaction, service quality, multiple linear regression.